The global burden and temporal trend of cancer attributable to high body mass index: Estimates from the Global Burden of Disease Study 2019 - Zhi, Xing; Kuang, Xiao-hong; Liu, Kuan; Li, Jian (Frontiers in Nutrition, 2022)
Objective: To describe the burden and temporal trend of cancer attributable to high body mass index (BMI), with major patterns highlighted by sex, Socio-demographic Index (SDI), and geographical region. Methods: This population-based observational study collected epidemiological data on cancer attributable to high BMI from the Global Burden of Diseases (GBD) 2019. The obtained data included deaths, disability-adjusted life-years (DALYs), and their age-standardized rates at the global, gender, SDI, regional, and country levels. The trend magnitudes and directions over time for mortality were analyzed. The associations between SDI and burden of cancer attributable to high BMI were also evaluated by Pearson correlation analysis. Results: Worldwide, 462.55 thousand deaths and 11.18 million DALYs of cancer were related to high BMI in 2019, and both have more than doubled since 1990. An annual 0.6% increase was observed for the age-standardized mortality rate (ASMR), and the rate of increase slowed after 2000. In general, the burden of cancer attributable to high BMI was heavier in regions with higher SDI levels, whereas the increase slowed down or even showed a decreasing trend in recent years. In contrast, in regions with lower SDI levels, although the baseline burden of cancer attributable to high BMI was relatively low, both the numbers and rates of deaths and DALYs showed a significantly increasing trend and may not stop increasing for a period of time. The trend and magnitude of high BMI-related cancer burden varied substantially in different anatomical sites. The leading three cancers of DALYs attributable to high BMI in 2019 were esophageal, colorectal and liver cancer. Conclusion: The high BMI-related burden of cancers is worsening, particularly in developing countries. Concerted action should be suggested to increase awareness of the harmful effects of high BMI and decrease the burden of disease attributable to high BMI, including cancer.